Evaluation of Library Services Circular Principles in the Scope of Public Library Services in Ankara - Şenol Karadeniz (Türk Kütüphaneciliği)
It was studied in the research if public libraries under the Ministry of Culture and Tourism in Ankara serve in accordance with the Circular of Library Service Principles. The troubles -if any- experienced during the implementation of the Circular and the possible reasons of those troubles were detected. Descriptive method was used in the research. Semi-structured interview technique was used to collect the data and the managers of the sample libraries were interviewed face-to-face. As a result of the research, it was found that public libraries sustain their traditional library services and mandatory administrative transactions generally related to public institutions in accordance with the Circular of Library Service Principles but the library services requiring more strategy, innovation and quality do not comply with the Circular due to several reasons. Some suggestions were presented for the related institutions.